Pandemic Crisis, its Health and Economic Determinants and Dampening Effects of Government Policies in EU Countries - Ochotnický, Pavol; Káčer, Marek; Belkovicsová, Daša; Ihnatišinová, Denisa (Ekonomika, 2025)
The COVID-19 pandemic shock resulted in a specific global health, social and economic multi-crisis, which was an unprecedented crisis in post-WW2 history. Both in terms of the devastating consequences on the health of the world’s population of sufferers, as well as on the extent of the impact on global economy. Based on the identified transmission channels of the pandemic into the economy and by using panel regression models, the contribution provides an explanation of the transmission of the pandemic to the health status of the population, to the labor supply, and subsequently, to a Type V recession. Based on these, the paper provides empirical evidence and policy recommendations that the government strictness in regulating population mobility, economic development of countries, population vaccination against COVID-19, and COVID fiscal health care spending were the main and most effective tools for reducing the live expectancy decrease in selected EU countries. To cushion the economic shock which the pandemic has directly had on the labor supply, the only effective anti-crisis fiscal instruments have been confirmed to be the effects of government capital spending, both in cushioning the recession and inflation.
Keywords: Pandemic shock; Global pandemic crisis; Excess mortality; Fiscal policy; COVID spending